Sustainable development analysis of design and manufacturing integration: A system dynamics approach. Issue 1 (1st January 2019) - Liu, Liyuan; Hsu, Yen; Lin, Jialiang
Abstract: The issue of the sustainability of design and manufacturing is dynamic, comprehensive and complex, and has always been a subject of discussion for scholars. This paper focuses on the sustainable issues of design and manufacturing and attempts to establish a system dynamics model combining design and manufacturing sustainability (CDMS). Through the method of system dynamics, Vensim software is used as the research tool, and the functions and influence proportions of the influencing variables are substituted into the model and then calculated. The information feedback mechanism and the causal cycle principle are used to simulate the development state of design and manufacturing. The results show that CDMS can smoothly present the interaction between design and manufacturing, and the variables are related to each other, showing the advantages of the CDMS model in analyzing the sustainable development of design and manufacturing. The research can provide further reference for follow-up research and practical application.